2014
DOI: 10.5860/crl12-423
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Inadequacy: A Study of the Imposter Phenomenon among College and Research Librarians

Abstract: The Imposter Phenomenon (IP) is an observed anxiety caused by an individual’s feelings of fraudulence, fear of being exposed as a fraud, and inability to internalize personal achievement. This study measures the incidence of the IP among librarians at college and research institutions in the United States and Canada and seeks to identify factors that contribute to its frequency. One in eight librarians reported above average IP scores. Younger librarians and those with less longevity experience IP feelings at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 14 publications
3
64
0
2
Order By: Relevance
“…Overall, these anecdotal findings tie in with the existing literature indicating that IS is damaging for both the individual who experiences it and their places of work, especially for those new to the profession (Clark and Barba, 2014). Hutchins (2015) even found that higher rates of IS thoughts in academic faculty were tied to lower ratings in job performance.…”
Section: Confronting Imposter Syndrome Through Guided Activitiessupporting
confidence: 71%
See 4 more Smart Citations
“…Overall, these anecdotal findings tie in with the existing literature indicating that IS is damaging for both the individual who experiences it and their places of work, especially for those new to the profession (Clark and Barba, 2014). Hutchins (2015) even found that higher rates of IS thoughts in academic faculty were tied to lower ratings in job performance.…”
Section: Confronting Imposter Syndrome Through Guided Activitiessupporting
confidence: 71%
“…As has been found by Faulkner (2015), while IS is not unique to new or younger librarians, it is greatly felt by this group in particular (Clark, Vardeman, & Barba, 2014). There are many reasons for this.…”
mentioning
confidence: 87%
See 3 more Smart Citations